Religion, Personality, and Mental Health - Brown, Laurence B. (Recent Research in Psychology, 1994)
The data from longitudinal studies presented in Religion, Personality and Mental Health indicate that there is no evidence of a consistent link between religiosity and pathology. Psychiatrists have traditionally used religious examples to illustrate such categories as catatonic posturing, delusions and depression. A close look at the role of religion in people's lives, however, shows that religious beliefs and practices have benefits as well as costs for psychological functioning. This book, which includes chapters on religion and counseling, happiness, religious lifestyles and mental health, the role of prayer, women religious professionals and stress, with data from a variety of studies and a review of the literature, will interest a wide range of researchers and practitioners